Acquisition of Early Developmental Milestones and Need for Special Education Services in Pediatric Multiple Sclerosis. (March 2019) - Aaen, Gregory; Waltz, Michael; Vargas, Wendy; Makhani, Naila; Ness, Jayne; Harris, Yolanda; Casper, T. Charles; Benson, Leslie; Candee, Meghan; Chitnis, Tanuja; Gorman, Mark; Graves, Jennifer; et al.
Children with pediatric-onset multiple sclerosis and pediatric controls were enrolled across 16 pediatric multiple sclerosis centers in the United States and completed questionnaires that addressed time of first unaided walking and acquisition of 2-word phrases. A total of 467 (308 female) cases and 428 (209 female) controls were enrolled. Pediatric multiple sclerosis (n = 467) were not delayed in walking or using 2-word phrases compared to healthy controls (n = 428) (2.2% vs 5.7%, respectively). Children with disease onset before age 11 versus onset at 11 years or after were more likely to need an individualized education plan ( P = .002), reading assistance ( P = .0003), and math assistance ( P = .001). Children with multiple sclerosis onset prior to age 18 are not delayed in meeting the 2 major early developmental milestones but do have a significantly increased use of special services or learning assistance at school. Further research will need to address whether other measures of development (eg, rate of language acquisition or fine motor skills) differ between pediatric multiple sclerosis and controls.